Distribution of Sylvia warblers at a stopover site during spring - Berglund, Hasse; Fransson, Thord (Ornis Svecica, 1993)
In this study the vertical and horizontal distribution of four Sylvia warblers at a spring stopover site on southernmost Gotland in the Baltic was investigated. The results show that there is some species specificity in micro-habitat choice, though small differences were found concerning the vertical distribution. During the breeding season, Sylvia warblers exhibit interspecific interactions to some degree, especially between the Garden Warbler S. borin and the Blackcap S. atricapilla. No change in habitat choice was noted in the distribution of Blackcaps after the arrival of Garden Warblers. This does not indicate that there is interspecific competition between these species during migration. However, the birds pass quickly through this stopover site and the situation may be different at a site where they stay longer. Some bird species were concentrated in particular nets, or groups of nets, which could be a warning when interpreting ringing results between years, since removal or addition of critical nets could highly affect the number of birds captured between years.